Nonthermal turbulent flow ultraviolet-C (UV-C) radiation processing for cheese whey-brines purification - Neokleous, Ioanna; Tarapata, Justyna; Papademas, Photis (My University, 2022)
The effect of ultraviolet C (UV-C) light technology on whey-brine inoculated with five different pathogens (or surrogates) was examined: Listeria innocua (NCTC 11288), Staphylococcus aureus (NCTC 6571), Bacillus cereus (NCTC 7464), Escherichia coli (NCTC 9001) and Salmonella enteritidis (NCTC6676). The most resistant microorganism was L. innocua, requiring a UV-C dosage of 320 J/L. The inactivation for the rest of the bacteria occurred at equal or less than 200 J/L dosage. The results from this study indicate that a continuous (UV-C) turbulent flow photo-purification processing system is a promising nonthermal processing method for the reduction of foodborne pathogens in turbid fluids (i.e. whey).
Keywords: Microbial inactivation; Nonthermal methods; UV-C technology; Whey